Anti-angiogenic effect of polygonum species: a comprehensive review of literature - Najla’ Shakirah Ab Halim,; Sheril June Ankasha,; Aslah Nabilah Abdull Sukor,; Nur Najmi Mohamad Anuar,; Norhazlina Abdul Wahab,; Shahidee Zainal Abidin,; Azizah Ugusman,; Adila A Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Angiogenesis is a physiological, tightly regulated process which is characterized by the development of new blood vessels. Compounds with the potential to control angiogenesis would be highly valuable as therapeutics, as an imbalance in angiogenesis may lead to several pathological disorders, including cancer, retinopathy, and arthritis. In this study, the anti-angiogenic effect of Polygonum sp. has been comprehensively reviewed and this plant also has been known to possess other medicinal benefits such as antioxidative, anti-inflammatory, anti-proliferative, and anti-tumor agents. Hence, this study systematically identified the evidence reporting the anti-angiogenic effects of Polygonum sp. Four electronic databases, namely PubMed, Ovid MEDLINE, Scopus and Web of Science were searched for relevant articles. Based on the pre-set eligibility criteria, 50 relevant articles were identified, and ten qualified articles were selected and reviewed. It was demonstrated that four namely P. cuspidatum, P. barbatum, P. hydropiper, and P. perfoliatum showed anti-angiogenic activities mainly through inhibition of the vascular endothelial growth factor-signaling pathways. Therefore, these species Polygonum have the potential to be developed as natural anti-angiogenic agents for prevention and treatment of various diseases related to pathological angiogenesis.